Enhancing Student Abilities through Couple Card Media in Connected Hijaiyah Learning with PBL Learning Model - Rohmat, Asep Saepul; Nasihudin, Nasihudin (Al-Aulad: Journal of Islamic Primary Education, 2023)
The study aimed to enhance student abilities through the use of Couple Card Media in Connected Hijaiyah Learning with the Problem Based Learning (PBL) model. Classroom Action Research was employed as the research method. Initial observations revealed varying test scores, with the highest at 90 and the lowest at 40, resulting in an average score of 53.00. Initially, 9 students (32.14%) achieved proficiency in the Connected Quranic Alphabet Learning Sub Connected Letters material, while 19 students (67.85%) did not. In Cycle II, using the Problem Based Learning model, 15 students (53.57%) reached proficiency, while 13 students (46.42%) did not, falling short of the minimum classical attainment indicator of 46%. By the end of Cycle III, test scores ranged from 60 to 95, with an average score of 77.50. In Cycle III, 24 students (85.71%) demonstrated proficiency in the "Connected Hijaiyah Letters" material, while 4 students (14.29%) did not.